EMPOWERING EDUCATIONAL COMMUNITIES: INNOVATION AND POSITIVE IMPACT THROUGH COMMUNITY SERVICE PROGRAMS - Abdurahman, Ayi (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Community service in education through community service programs is the main focus of this article. This purpose of service illustrates efforts to empower the educational community through innovation and positive impact. The service method uses a participatory action research (PAR) approach through participatory and collaborative methods, which is applied to identify specific needs in the educational community, involving teachers, students, parents, and the local community. Community service activities will be carried out from July to September 2023. The service results include increased active involvement from stakeholders, positive changes in teaching methods, and adopting innovations at the educational institution level. Beyond providing assistance, the program creates sustainable change in the education ecosystem, demonstrating that innovation and active collaboration are key to strengthening and empowering the education community. This article provides practical and inspiring insights for educational institutions and communities to adopt similar approaches to achieve a significant positive impact in improving the quality of education.